Synthesis of Methylene‐Bridged Bisnaphthalenes as Building Blocks for Push–Pull Substituted Pentacenes. Issue 47 (20th December 2017) - Wagner, Frederic; Harms, Klaus; Koert, Ulrich
Abstract : The use of cross‐coupling reactions for the synthesis of methylene‐bridged bisnaphthalenes bearing two nitro groups on one naphthalene and two amino groups on the other has been investigated. A Hauser–Heck reaction was used to prepare the substituted naphthalene building blocks. It was not possible to install a transmetallating function in the benzylic position due to side reactions with the nitro and the amino groups. A successful Suzuki reaction was achieved by using naphthyl trifluoroborates and bromomethyl naphthalenes. The resulting dinaphthyl methanes could be useful for the synthesis of push–pull substituted pentacenes. Abstract : The regioselective synthesis of methylene‐bridged substituted bisnaphthalenes is reported. Successful Suzuki reactions were achieved by using naphthyl trifluoroborates and bromomethylnaphthalenes.